2018
DOI: 10.1038/s41467-018-07320-9
|View full text |Cite
|
Sign up to set email alerts
|

Energy landscape underlying spontaneous insertion and folding of an alpha-helical transmembrane protein into a bilayer

Abstract: Membrane protein folding mechanisms and rates are notoriously hard to determine. A recent force spectroscopy study of the folding of an α-helical membrane protein, GlpG, showed that the folded state has a very high kinetic stability and a relatively low thermodynamic stability. Here, we simulate the spontaneous insertion and folding of GlpG into a bilayer. An energy landscape analysis of the simulations suggests that GlpG folds via sequential insertion of helical hairpins. The rate-limiting step involves simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…A recent GlpG force-induced unfolding study concluded that the two-stage membrane folding model (44) is overly simplistic because isolated helices can coexist with a folded domain, and all the helices do not have to be in the bilayer before the initiation of folding (45). Although our study reproduces these two items, some technical differences between the two studies are worth noting.…”
Section: Discussionmentioning
confidence: 70%
“…A recent GlpG force-induced unfolding study concluded that the two-stage membrane folding model (44) is overly simplistic because isolated helices can coexist with a folded domain, and all the helices do not have to be in the bilayer before the initiation of folding (45). Although our study reproduces these two items, some technical differences between the two studies are worth noting.…”
Section: Discussionmentioning
confidence: 70%
“…Simulations can play a vital role in helping to rationalize the folding and assembly mechanism of membrane proteins. Some elegant examples include the use of coarse-grained models to study the mechanism of GlpG folding [13], or to predict the topology of multi-pass transmembrane helical proteins [14]. Studying the details of the helix assembly into the specific native structure, however, requires a higher-resolution model.…”
Section: Introductionmentioning
confidence: 99%
“…Point mutations in an upstream TMH can affect the pulling force generated by downstream TMHs in a highly position-dependent manner, suggestive of residue-specific interactions between TMHs during the membrane-integration process. Complementing in vitro unfolding/folding studies (27,28), real-time FRET analyses (15), chemical crosslinking (29), structure determination (30), and computational modeling (31), high-resolution in vivo FPA can help identify the molecular interactions underlying cotranslational membrane protein biogenesis with single-residue precision. For constructs with N≥298, the C-terminal tail is 75 residues long.…”
mentioning
confidence: 99%